Simulation and Performance Test Giromill Type Wind Turbine; Case Study Muara Enim, South Sumatra, Indonesia - Ovi Irawan; Yohandri Bow; RD Kusumanto (International Journal of Research in Vocational Studies (IJRVOCAS), 2021)
This research examines the dynamic load resistance of the Giromill type wind turbine to the variable wind speed, which is converted to the value of the force received by the wind turbine blades. The analysis was carried out numerically using Autodesk Inventor Professional 2019 software. The variations in wind speed used were 2.5 m/s with a force value of 0.195 N for the Giromill turbine, at a speed of 3.5 m/s with a force value of 0.274 N, at 4.5 m /s with a Force value of 0.352 N and a wind speed of 5.5 m/s with a force rating of 0.430 N. From the simulation results using the Autodesk Inventor Pro 2019 software, the effect of gravitational force is greater than the wind force in, so stress analysis is mainly caused by gravity while the wind force has no significant impact. The simulation results also have a characteristic that the higher the wind speed, the lower the stress value. In addition to the dynamic load simulation, the author also tries to implement the Giromill wind turbines in Muara Enim district, South Sumatra, Indonesia. The wind turbine blade rotation will be faster, and the Wind Generator will produce a greater voltage if it is supported by sufficient wind speed.